Needs Analysis on the Development of Ethnomedicine Books as a Student Learning Resource in Ethnobotany Courses - Ummi Zaimah; Ashar Hasairin; Diky Setya Diningrat (Magister Pendidikan Biologi, Universitas Negeri Medan, 2022)
Book development is very important to do support the learning process because it is integrated with the competencies that must be mastered and learned by students. The first step before developing the book is to conduct a needs analysis. This activity aims to determine the level of student need for the availability of books as learning resources used during ethnobotany lectures on ethnomedicine material. This research was conducted on 35 student of biology at the State University of Medan. This research is a qualitative descriptive study using a survey method. Data collection was carried out using a closed questionnaire. The results showed that the analysis of learning materials, as many as 62.9% of respondents said that ethnomedicine is one of the difficult materials in ethnobotany courses. The highest percentage is when identifying plants used as medicine (54.3%). Based on the needs analysis, 54.3% of respondents needed ethnomedicine books to add insight, so that 51.4% of respondents strongly agreed to develop ethnomedicine books as learning resources. It can be concluded that it is necessary to develop an ethnomedicine book as a learning resource that is prepared based on student needs and adapted to the sub-CPMK of ethnobotany subjects on ethnomedicine material. This research is useful to determine the need for learning resources needed to overcome the problems faced by students in learning activities so that the products developed are in accordance with the needs of students.